166k views
4 votes
neX + 6Let f(x) = 3x - 6, h(x) =3frEvaluate (f o h)(6).The composite function (f o h) evaluated at x = 6 is, (foh)(6) =

neX + 6Let f(x) = 3x - 6, h(x) =3frEvaluate (f o h)(6).The composite function (f o-example-1
User Zeema
by
5.2k points

1 Answer

4 votes

\begin{gathered} f(x)=3x-6 \\ \\ h(x)=(x+6)/(3) \end{gathered}

first we make (foh)(x)


foh(x)=3((x+6)/(3))-6

simplify


\begin{gathered} foh(x)=x+6-6 \\ foh(x)=x \end{gathered}

now replace x=6


foh(6)=(6)

So, the composite function (foh) evaluated at x=6 is,(foh)(6)=6

User Salman Raza
by
5.3k points